Adult Acute Lymphocytic Leukemia Biology and Treatment - Advani, Anjali S.; Lazarus, Hillard M.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2011)
The current explosion of new areas of controversy in the treatment of acute lymphocytic leukemia in adults and young adults makes this comprehensive book a much needed reference for hematologists and oncologists. This book assembles leading authorities from around the globe to cover the full spectrum of ALL subtypes and their treatments. Specific topics of discussion include indications for allogeneic bone marrow transplant in first complete remission, the role of minimal residual disease in making treatment decisions, the treatment of young adults, and the treatment of Philadelphia chromosome positive ALL with the advent of the tyrosine kinase inhibitors. This is the first book to focus exclusively on the adult ALL patient. It provides a complete overview of diagnosis, molecular pathogenesis, evaluation, and treatment for this important patient population.
A Perspective on the Treatment of Acute Lymphoblastic Leukemia -- Clinical Features and Making the Diagnosis -- The Biology of Adult Acute Lymphoblastic Leukemia -- Minimal Residual Disease in Acute Lymphoblastic Leukemia -- Cytogenetics -- Acute Lymphoblastic leukemia: Epidemiology -- Prognostic Factors in Acute Lymphoblastic Leukemia -- The Generalized Care of the Patient with Acute Lymphoblastic Leukemia -- Treatment of Acute Lymphoblastic Leukemia in Middle-Age and Older Adults.-Pharmacology of Acute Lymphoblastic Leukemia Therapy -- Assessment of Response to Treatment -- T-cell Acute Lymphoblastic Leukemia -- Burkitt Leukemia and Lymphoma -- Treatment of Acute Lymphoblastic Leukemia in Young Adults Nicolas Boissel -- Treatment of Philadephia Chromosome Positive Acute Lymphoblastic Leukemia -- Molecular Therapies -- Treatment of Relapsed/ Refractory Acute Lymphoblastic Leukemia -- Allogenic Stem Cell Transplantation for Acute Lymphoblastic Leukemia in Adults -- Hematopoietic Stem Cell Transplantation in Philadelphia-positive Acute Lymphoblastic Leukemia -- Special Challenges: Genetic polymorphisms and therapy -- Late Consequences of Therapy of Acute Lymphoblastic Leukemia -- Immunotherapy for Acute Lymphocytic Leukemia -- Unique Subtypes in Acute Lymphoblastic Leukemia.
Keywords: Medicine; Hematology; Oncology; Medicine & Public Health; Hematology; Oncology